2021
DOI: 10.18251/ijme.v23i1.2435
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Curriculum of Monolingualism: Understanding Metonymy to Interrogate Problematic Representations of Raciolinguistic Identities in Schoolscapes

Abstract: Choices regarding how signs are displayed in schools send messages regarding the status of languages and speakers of those languages.  The monolingual paradigm can be implicitly reified by the position, shape, color, etc. of languages in relation to English on school signage (Author & Co-author, 2018).  This can have a negative impact for culturally and linguistically diverse youth.  In combining critical race media literacy with linguistic landscape research, we uncover a hidden media of raciolinguistic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Thus, offering more university programming and initiatives (e.g., counseling services, tutoring, advising, NSO, affinity groups) led by Spanish-speaking faculty, staff, and students can contribute to Latine students' linguistic capital as well as potentially serve as an avenue for cognitive resilience and social capital. Przymus and Huddleston (2021) caution schools to contemplate the covert messages and effects of bilingual signage on campuses. Evaluating the location, size, context, and color of bilingual signage can reveal unconscious biases about the value of a language and lead to identifying ways to promote shared linguistic and other forms of social capital.…”
Section: Implications For Practicementioning
confidence: 99%
“…Thus, offering more university programming and initiatives (e.g., counseling services, tutoring, advising, NSO, affinity groups) led by Spanish-speaking faculty, staff, and students can contribute to Latine students' linguistic capital as well as potentially serve as an avenue for cognitive resilience and social capital. Przymus and Huddleston (2021) caution schools to contemplate the covert messages and effects of bilingual signage on campuses. Evaluating the location, size, context, and color of bilingual signage can reveal unconscious biases about the value of a language and lead to identifying ways to promote shared linguistic and other forms of social capital.…”
Section: Implications For Practicementioning
confidence: 99%
“…This section asks educators to critically analyze schoolscapes (Brown, 2012), or the school ground's message boards, hallways, classroom walls, etc. and bilingual books used in the classroom, for hierarchical language use that positions some languages (and by default the speakers of those languages) as more or less important (Przymus & Huddleston, 2021; Przymus & Lindo, 2021). Only after this critical reflection of the “school world” takes place, can we co‐engage with students in the “ writing it or rewriting it, that is, of transforming it by means of conscious, practical work” (Freire & Macedo, 2005, p. 23).…”
Section: Reading and Being Critical Consumers Of The World Of Schools...mentioning
confidence: 99%
“…Existing practice, results, and identities for students remain the same. Przymus and Huddleston (2021) conducted a critical multi-modal discourse analysis of the schoolscapes of 10 public elementary, middle, and high school campuses in the American South-Central that all advertised and promoted their bilingual (dual-language immersion) programs. Documenting the first 10 bilingual signs upon entering each of the 10 campuses, the researchers found that 96/100 signs (96%) privileged English via directional metonymy (English listed first or on top of the Spanish), 77/100 (77%) also made English stand in place for more value and prominence via font style metonymy (English letters bigger, bold, not italicized, in blue vs. red, etc.)…”
Section: Bilingual Schoolscapes?mentioning
confidence: 99%